ANALISIS FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Andy Priyono (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2018)
Going concern audit opinion received by a company auditor shall indicate their doubts viability of the company. Going concern audit opinion can be used a basis for decision making for users. Some study on the factors that may affect the auditor's going concern audit opinion has been done. However, results of these studies still show inconsistency. This study aims to reexamine the factors that affect the going concern audit opinion.In this study to examine the effect of leverage, liquidity, financial condition, company growth, debt default, audit quality and an independent commissioner to the acceptance of going concern audit opinion. The study design was quantitative with the hypothesis. Test of hypothesis of the study is the logistic regression analysis. The samples of this study were manufacturing companies listed in Indonesian Stock Exchange (IDX) for the period of 2010-2015. Data were collected using purposive sampling method.The results of this study show that the financial condition is an negative influence on the acceptance of going concern audit opinion while leverage and audit quality is an positive influance on the acceptance of going concern audit opinion. While liquidity, company growth, debt default and an independent commissioners is not influence on the acceptance of going concern audit opinion